THE ROLE OF BRAND RELIABILITY AND BRAND INTENTION IN MEDIATING THE RELATIONSHIP BETWEEN CUSTOMER SATISFACTION AND BRAND LOYALTY - Budi Setiawan; Ellisya Patricia (Kesatuan Press, 2022)
This study aims to fill the research gap regarding the role of brand reliability and brand intention in mediating the relationship between overall customer satisfaction on brand loyalty. The research context is on bottled drinking water customers who already know the brand name and have consumed products from the bottled drinking water brand name. The sampling technique used a non-probability sampling approach, namely purposive sampling. The sample size is 120 respondents by following the general rules of factor analysis. The study results revealed that brand intention has an essential role in mediating the effect of overall customer satisfaction on brand loyalty. Unfortunately, there is no data support regarding the mediating role of brand reliability.